PENGARUH KOMUNIKASI PEMASARAN DAN KERELASIAN NASABAH TERHADAP LOYALITAS NASABAH PADA BANK RAKYAT INDONESIA JEMBER - Syaiful Amin; Hary Sulaksono (RELASI : JURNAL EKONOMI, 2012)
In the particular business activity of banking, marketing communications is crucial to retaining customers and attract new customers. Similarly, a customer relations activities in order to maintain customer loyalty occurs relationship between the company and customer on an ongoing basis. This research aims to determine the direct effect simultaneously and partially between the marketing communication and customer relation to the customer loyalty at Bank Rakyat Indonesia Jember and to find out the most dominant exogenous variables in affecting to the endogenous variables. Subject of this research is Bank Rakyat Indonesia Cabang Jember. The analytical tool used in this research is the path analysis. The results of this research are exogenous variables which consists of marketing communications, customer relations, and customer response simultaneously influence on customer loyalty, but in partial customer relations does not have direct effect on customer loyalty, while variable marketing communications and customer response is partially affected on customer loyalty, meanwhile the customer response variable to be the most dominant variable in affecting customer loyalty.